Variable Herz estimates for fractional integral operators - Heraiz , R. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5 In this paper, the author study the boundedness of fractional integral operators on a variable Herz-type Hardy space HK^α (· )_p(· ),q(· )(R^n) by using the atomic decomposition.